Chinese M&A in Germany: Integration Approach and International Corporate Strategy - Berning, Sue Claire (2015 Academy of International Business South East Asia Regional Conference, 2015)

Chinese Outward Foreign Direct Investment – A Challenge for Traditional Internationalization Theories? - Berning, Sue Claire; Holtbrügge, Dirk; et al. (2012 Academy of International Business South East Asian Regional Chapter Meeting, 2012)

Chinese outward foreign direct investment - a challenge for traditional internationalization theories? - Berning, Sue Claire; Holtbrügge, Dirk (Journal für Betriebswirtschaft, 2012)
In this paper we explore the current state of research on outward foreign direct investment (OFDI) of Chinese firms. A literature review identifies 62 articles in 15 peer-reviewed academic journals that were published between 1986 and 2012. We examine the underlying theories, research methods, motives, determinants, host countries, industries, periods of observation, nationality of authors and performance of Chinese OFDI, as well as the degree of consensus with traditional internationalization theories. We find that the majority of studies find these theories not applicable to explain Chinese OFDI. We discuss possible extensions and modifications and derive implications for future research. © Wirtschaftsuniversität Wien, Austria 2012.
WiSo-Import:2015-03-26:3932
Keywords: Chinese MNEs; Chinese outward FDI; Emerging market firms; Internationalization theories

Email Communication Styles across Cultures - Holtbrügge, Dirk; Berning, Sue Claire (The International Encyclopedia of Intercultural Communication, 2017)
Email communication is recognized as the most often used communication method in international companies' operations. This computer‐mediated communication technology constitutes a further layer of intercultural communication in the global workplace. Variations in email communication styles exist due to cultural differences and can be explained by E. T. Hall's dimensions of context, time, and space orientation. Particularly, cultural background has a significant impact on the preference for formalness, promptness, preciseness, task orientation, and relationship‐relatedness in email communicati
Keywords: Intercultural Communication

Indigenous chinese management philosophies: Key concepts and relevance for modern chinese firms - Garg, Ritam; Berning, Sue Claire (Indigenous Studies: Breakthroughs in Research and Practice, 2019)
Increasing internationalization of Chinese firms is continuously attracting the attention of management scholars across the world. Hence, one of the main questions in this context is whether the unique cultural concepts that are indigenous to China support or aggravate the success of Chinese firms. The main objective of this study is therefore to review the cultural aspects prevalent in China from an indigenous management perspective. In particular, we explore whether and how the ancient Chinese teachings and philosophies, such as Guanxi or Mianzi, are relevant in the modern Chinese management context. This study specifically seeks to contribute to the understanding of management culture of Chinese firms and, more generally, to cross-cultural and indigenous management research. © 2020, IGI Global.
CRIS-Team Scopus Importer:2024-12-16

Market Entry Strategies and Performance of Chinese Firms in Germany: The Moderating Effect of Government Support - Berning, Sue Claire; et al. (Academy of International Business 2015 Annual Meeting, 2015)

Market Entry Strategies and Performance of Emerging Market Firms in Germany: The Moderating Effect of International Experience - Berning, Sue Claire; et al. (2015 European Academy of Management Conference, 2015)

Outward Foreign Direct Investment of Emerging Market Firms. - Berning, Sue Claire; et al. (Foreign Investment in Eurasia and the Pacific Rim, 2015)

Pictures as means of intercultural communication – The case of Chinese firms in Germany - Berning, Sue Claire; et al. (Yearbook of Market Entry Advisory 2015, 2016)

The national government's role in Chinese outward foreign direct investment - Holtbrügge, Dirk; Berning, Sue Claire (Research Handbook on the Globalization of Chinese Firms, 2014)
WiSo-Import:2015-04-20:5125

The Push and Pull Effects of Government Policies on Chinese Outward Foreign Direct Investment – A Literature Review - Berning, Sue Claire; Holtbrügge, Dirk; et al. (7th China Goes Global Conference, 2013)